The Relationship of Language Variation with Social Groups and Language Use in Perumnas Tanjung Karang Permai - Komang Ayu Gusta Arsyandi; Muhid, Abdul; Rahmawati, Lela (Jurnal Ilmu Sosial dan Humaniora, 2022)
This study discusses Language Variations in Perumnas. In the research method, the data were analyzed based on the definition of descriptive qualitative method with the data technique of Simak Libat Bebas Cakap (SLBC), Recording technique,Observation and Note taking Technique. This study uses the theory of Sudaryanto (1993) regarding the method Simak. The conversations of the Perumnas social group were analyzed. Then each word in the conversation is classified based on the type and the causal factor. After analyzing the researcher explained the data found later and concluded this research. From several aspects that have been mentioned in Language Variations in chapter two, there are several types of language variations used in Perumnas 4 formal data variety, 9 data variety informal, 10 data variety Casual,3 data variety Intimate, and 1 data variety Consultative.